Occurrence of Subclinical Atrial Fibrillation in the Follow-up of Patients with Cardiac Pacemakers - Brunello, Luis Fernando Spagnuolo; Figueiredo, Gustavo Andrade de; Mulinari, Leonardo Andrade (JOURNAL OF CARDIAC ARRHYTHMIAS, 2019)
Objective: Cardiac pacemaker records atrial fibrillation (AF). This condition can cause serious hemodynamic consequences to patients, who should be assisted by a cardiologist. This study aimed to document and investigate, in a tertiary hospital, the prevalence of subclinical AF in patients with a cardiac pacemaker. Methods: Between July 2015 and April 2016, 196 patients with pacemakers were attended on an outpatient basis. Of these, 60 had cardiac arrhythmias recorded by the pacemaker and were invited to participate in the study. Data collection was done through a structured interview containing four questions: gender, age, follow-up with cardiologist and use of anticoagulants. Results: Subclinical AF was recorded in 35 (17.8%) of the total of 196 patients. Of these 35, 16 (45.7%) did not follow a regular cardiology service and 29 (82.8%) did not use anticoagulant medication. No statistically significant relationships were found between age, follow up with a cardiologist, and presence or absence of subclinical AF in the patients studied. Conclusion: A significant portion of outpatient patients with pacemakers have AF recorded by the device. However, although essential, almost half of these do not proceed with the clinical follow-up with cardiologist and less than a fifth with AF makes use of anticoagulant therapy.